Identifying Geriatric Oncology Competencies for Medical Oncology Trainees: A Modified Delphi Consensus Study. (1st April 2020) - Hsu, Tina; Kessler, Elizabeth R.; Parker, Ira R.; Dale, William; Gajra, Ajeet; Holmes, Holly M.; Maggiore, Ronald J.; Magnuson, Allison; McKoy, June M.; Hurria, Arti
Abstract: Background: Most oncology trainees are not taught about the needs of older patients, who make up the majority of patients with cancer. Training of health care providers is critical to improve the care of older adults with cancer. There is no consensus about which geriatric oncology (GO) competencies are important for medical oncology trainees. Our objective was to identify GO competencies medical oncology trainees should acquire during training. Materials and Methods: A modified Delphi consensus of experts in oncology medical education and GO was conducted. Experts categorized at what training stage proposed competencies should be attained: internal medicine, oncology, or GO training. Consensus was obtained if two thirds of experts agreed on the training stage at which the competency should be attained. Results: A total of 78 potential competencies were identified, of which 35 (44.9%) proposed competencies were felt to be appropriate to be acquired during oncology training. The majority of the identified competencies pertained to prescribing of systemic therapy ( n = 12) and psychosocial and supportive care ( n = 13). No competencies related to geriatric assessment were identified for acquisition during oncology training. Conclusion: Experts in oncology education and geriatric oncology agreed upon a set of GO competencies appropriate for oncology trainees. These results provide the foundation for developing a GO curriculum for medical oncology trainees and will hopefully lead to better care of older adults with cancer. Implications for Practice: The aging population will drive the projected rise in cancer incidence. Although aging patients make up the majority of patients diagnosed with cancer, oncologists rarely receive training on how to care for them. Training of health care providers is critical to improving the care of older adults with cancer. The results of this study will help form the foundation of developing a geriatric oncology curriculum for medical oncology trainees. Abstract : Training of health care providers is critical to improving the care of older adults with cancer. This article focuses on the geriatric oncology competencies an oncology trainee should possess on completion of training and provides a foundation for development of a geriatric oncology curriculum for medical oncology trainees.